2018
DOI: 10.1016/j.ijheh.2017.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Increased cancers among residents living in the neighborhood of a petrochemical complex: A 12-year retrospective cohort study

Abstract: This study investigates whether cancers are increased for residents living in the vicinity of a petrochemical complex with coal power plants and refineries. We recruited a residential cohort of 2388 long-term residents aged above 35 years in 2009-2012 who lived within a 40 km radius of the complex. We measured their internal exposure biomarkers of urinary carcinogenic metals and retrospectively compared cancer incidences between those who lived fewer than 10 km from the complex (high exposure, HE) and those wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…The young are especially susceptible due to their still developing physique as well as immature lungs and immune systems (Branco et al, 2014;Esposito et al, 2014;Korten et al, 2017). Prolonged exposure to high levels of air pollutants may increase the risk of developing cancer especially for those living near to heavy industries (Tsai et al, 2009;Yuan et al, 2018;Seifi et al, 2019). Many epidemiological studies have convincingly demonstrated the deterioration of air quality in schools in the proximity of big industrial areas, which has led to significant respiratory health impacts especially of the acute nature (de Moraes et al, 2010;Godoi et al, 2013;Demirel et al, 2014;Rovira et al, 2014;Suhaimi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The young are especially susceptible due to their still developing physique as well as immature lungs and immune systems (Branco et al, 2014;Esposito et al, 2014;Korten et al, 2017). Prolonged exposure to high levels of air pollutants may increase the risk of developing cancer especially for those living near to heavy industries (Tsai et al, 2009;Yuan et al, 2018;Seifi et al, 2019). Many epidemiological studies have convincingly demonstrated the deterioration of air quality in schools in the proximity of big industrial areas, which has led to significant respiratory health impacts especially of the acute nature (de Moraes et al, 2010;Godoi et al, 2013;Demirel et al, 2014;Rovira et al, 2014;Suhaimi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…8 Further to that, cancer has been associated with living near oil refinery but the results are not consistent. [11][12][13] There is limited data from the Middle East on health impact of living near an oil refinery.…”
Section: Introductionmentioning
confidence: 99%
“…45 Specifically, high urinary arsenic levels associate with anti-HAV seroprevalence, HEV seroconversion during pregnancy, elevated risk of hepatitis B infection, and higher prevalence rates of hepatitis C in petrochemical complex area. [49][50][51][52] Finally, increased urinary arsenic levels associates positively with elevated serum concentrations of biomarkers for NAFLD (ALT enzyme), suggesting a higher risk to this disease in Mexican Americans in the US. 53 Consistently, the presence of heavy metal contamination including iAs in soils increased the risk for NAFLD in men with a body mass index (BMI) <24, reinforced the proposal that arsenic exposure is a risk factor for NAFLD occurrence.…”
Section: Epidemiologymentioning
confidence: 99%